Pengaruh Kemiskinan Dan Pengangguran Terhadap Pertumbuhan Ekonomi Di Provinsi Bali Tahun 2002-2021 - Ahadi Akbar Fajri; Ririt Iriani (Ekopem: Jurnal Ekonomi Pembangunan, 2022)
The prosperity and welfare of the people of a country is the result of economic growth which is a visual representation and main indicator of a country's economic health. The purpose of this study was to determine the effect of poverty and unemployment on economic growth in Bali Province in 2002-2021. This study uses secondary data, namely time series data from 2002-2021. The analytical tool used in this research is multiple linear regression analysis using SPSS26 software. The results showed that partially poverty had a significant positive effect on economic growth, while unemployment had a significant negative effect on economic growth in Bali Province. Simultaneously poverty and unemployment have a significant positive effect on economic growth in the Province of Bali.